2016
DOI: 10.1007/s00360-016-0965-5
|View full text |Cite
|
Sign up to set email alerts
|

The transition from water-breathing to air-breathing is associated with a shift in ion uptake from gills to gut: a study of two closely related erythrinid teleosts, Hoplerythrinus unitaeniatus and Hoplias malabaricus

Abstract: The evolutionary transition from water-breathing to air-breathing involved not only a change in function of the organs of respiratory gas exchange and N-waste excretion, but also in the organs of ion uptake from the environment. A combination of in vivo and in vitro techniques was used to look at the relative importance of the gills versus the gut in Na(+), Cl(-), and K(+) balance in two closely related erythrinid species: a facultative air-breather, the jeju (Hoplerythrinus unitaeniatus) and an obligate water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This suggests that, compared to water breathing teleosts, the gills of A. gigas are of reduced importance for ion uptake and ion homeostasis. This is in line with our measurements of Na + /K + -ATPase activity and also of V-ATPase activity in gill tissue and ABO, which revealed that the activity of both ATPases compared to activities recorded in water breathing fish or even the air-breathing Hoplerythrinus unitaeniatus are particularly low, pointing to a low ion exchange capacity of A. gigas gills, in small as well as in larger fish [8,27]. In accordance, the gills' oxygen uptake of A. gigas is lower compared to the water-breathing brown trout (Salmo trutta) [28].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that, compared to water breathing teleosts, the gills of A. gigas are of reduced importance for ion uptake and ion homeostasis. This is in line with our measurements of Na + /K + -ATPase activity and also of V-ATPase activity in gill tissue and ABO, which revealed that the activity of both ATPases compared to activities recorded in water breathing fish or even the air-breathing Hoplerythrinus unitaeniatus are particularly low, pointing to a low ion exchange capacity of A. gigas gills, in small as well as in larger fish [8,27]. In accordance, the gills' oxygen uptake of A. gigas is lower compared to the water-breathing brown trout (Salmo trutta) [28].…”
Section: Plos Onesupporting
confidence: 90%
“…This is in line with our measurements of Na + /K + -ATPase activity and also of V-ATPase activity in gill tissue and ABO, which revealed that the activity of both ATPases compared to activities recorded in water breathing fish or even the air-breathing Hoplerythrinus unitaeniatus are particularly low, pointing to a low ion exchange capacity of A . gigas gills, in small as well as in larger fish [ 8 , 27 ]. In accordance, the gills' oxygen uptake of A .…”
Section: Discussionmentioning
confidence: 99%
“…Although the whole procedure was completed within 2 or 3 min, oxygen could have been removed from the bladder during this time and not replaced, resulting in lower oxygen values. In a previous study, we measured an oxygen uptake of 5.6 ± 0.6 µmol g − 1 h − 1 for jeju at a temperature of 29–32 °C (Wood et al 2016 ). Therefore, a 100 g of jeju would consume about 19 µmol of oxygen within 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…Rather they decrease ion fluxes and N-waste excretion rates across the gills during aquatic hypoxia by selective reductions in branchial permeability, without apparently compromising the capacity for O 2 uptake. Most importantly, a facultative air-breathing Amazonian teleost, the jeju (Hoplerythrinus unitaeniatus) was able to simply avoid the gillperturbing effects of both aquatic hypoxia and aquatic hyperoxia by resorting to air-breathing (Wood et al, 2016). Therefore, our fourth and final hypothesis was that A. gigas would be able to avoid the symptoms of the osmorespiratory compromise at the gills during aquatic and aerial hypoxia and hyperoxia.…”
Section: Introductionmentioning
confidence: 96%